Using AHP-GIS for land suitability of Banggai Yam development in Banggai Island, Indonesia - Katili, Hidayat Arismunandar; Widiatmaka, Widiatmaka; Syartinilia, Syartinilia; Firmansyah, Irman (Brawijaya University, 2025)
A major challenge for the country is ensuring sufficient food production to meet the demands of its growing population. To address this issue, it is essential to enhance local root crop production as future food security. This study aims to assess the available and suitable land for Banggai Yam cultivation. The Multicriteria Evaluation Method was utilized to evaluate land suitability, while land availability was determined by integrating land use and land cover actual, forest area, and spatial pattern maps. The analysis revealed that 99,197 hectares are available for crop development. Expert assessment using the Analytic Hierarchy Process identified key land parameters such as cation exchange capacity, Base saturation, texture, and climatic factors like rainfall vital for determining land suitability, totaling 232,250.7 hectares. The combined maps indicated 95,301.6 hectares as potential development areas, with highly suitable land at 2.8%, moderately suitable land at 29%, and marginally suitable land at 8.3%. Conversely, land classified as unsuitable for cultivation constitutes 59.9%. These findings provide valuable insights for government officials, farmers, and researchers to optimize land use for these crops as a means to meet national food requirements.